Effect of aqueous extracts of Ficus vogeliana Miq and Tieghemella africana Pierre in 7, 12-Dimethylbenz(a)anthracene -induced skin cancer in rats. (5th December 2020) - Ngoua Meye Misso, Rick-Léonid; Nsole Biteghe, Fleury Augustin; Obiang, Cédric Sima; Ondo, Joseph-Privat; Gao, Nan; Cervantes-Cervantes, Miguel; Vignaux, Guillaume; Vergeade, Aurelia; Engohang-Ndong, Jean; Mendene, Hugue Ella; Mabika, Barthelemy; Abessolo, Félix Ovono; et al.
Abstract: Ethnopharmacological relevance: Skin cancer is the most common form of cancer responsible for considerable morbidity and mortality. Tieghemella africana and Ficus vogeliana are used in traditional medicine to treat cancers. Aim of the study: Therefore, the aim of this study was to investigate the antioxidant, antiangiogenic and anti-tumor activities of these plant extracts. Materials and methods: To achieve it, phytochemical screening, antioxidant activity and antiangiogenic activity were assessed. Thereafter, the anti-tumor activity was determined using skin tumorigenesis induced by 7, 12-dimethylbenz[a]anthracene. Results: The phytochemical result analysis showed that both plant extracts were rich in polyphenols, alkaloids and terpene compounds and possessed good antioxidant activity based on DPPH radical scavenging (IC50 = 9.70 μg/mL and 4.60 μg/mL and AAI values of 5.20 and 10.88) and strong total antioxidant capacity (115.44 VtCE (mg)/g of dry plant extract and 87.37 VtCE (mg)/g of dry plant extract, respectively). Additionally, both plant extracts possessed antiangiogenic activities (IC50  = 53.43 μg/mL and 92.68 μg/mL, respectively), which correlated with significant antitumor activities when using 35 mg/kg (65.02% and 77.54%) and 70 mg/kg of extracts (81.07% and 88.18%). Conclusions: In summary, this study illustrates the promising usage of Tieghemella africana and Ficus vogeliana plant extracts in treating skin cancer. However, further characterization of the extracts must be performed to isolate the most active anticancer compound. Graphical abstract: Image 1